NFAT regulates pre-synaptic development and activity-dependent plasticity in Drosophila. - Freeman, A.; Franciscovich, A.; Bowers, M.; Sandstrom, D.J.; Sanyal, S. (Molecular and Cellular Neurosciences, 2011)
The calcium-regulated transcription factor NFAT is emerging as a key regulator of neuronal development and plasticity but precise cellular consequences of NFAT function remain poorly understood. Here, we report that the single Drosophila NFAT homolog is widely expressed in the nervous system including motor neurons and unexpectedly controls neural excitability. Likely due to this effect on excitability, NFAT regulates overall larval locomotion and both chronic and acute forms of activity-dependent plasticity at the larval glutamatergic neuro-muscular synapse. Specifically, NFAT-dependent synaptic phenotypes include changes in the number of pre-synaptic boutons, stable modifications in synaptic microtubule architecture and pre-synaptic transmitter release, while no evidence is found for synaptic retraction or alterations in the level of the synaptic cell adhesion molecule FasII. We propose that NFAT regulates pre-synaptic development and constrains long-term plasticity by dampening neuronal excitability.